A multi-faceted approach to sex and gender equity in solid organ transplantation: The Women in Transplantation Initiative of The Transplantation Society - Mannon, Roslyn B.; Reed, Elaine F.; Melk, Anette; Vinson, Amanda; Wong, Germaine; Ahn, Curie; Davidson, Bianca; Foster, Bethany; West, Lori J.; Tait, Katie; Chong, Anita S. (Frontiers in Immunology, 2022)
The advancement of women’s careers in transplantation continues to be challenging. Academic careers in both basic and clinical disciplines in transplantation, such as surgery and management of end organ failure in medical specialties, have been underrepresented by diverse genders and ethnicities. Over the last decade, the Women in Transplantation Initiative (WIT) has solidified to becoming an internationally recognized organization with activities focused on diversity and inclusion in terms of the sexes. The WIT organization is divided into 3 pillars that address career advancement and networking (Pillar 1), scientific investigation and presentations on sex and gender in transplantation (Pillar 2) and investigating and facilitating equitable access to transplantation for women throughout the world (Pillar 3). By taking this multipronged approach of collaborating across continents, leveraging virtual platforms for information dissemination and discussion, and providing financial support for research, WIT has become a highly visible grass roots organization that aims to improve the experience of women as transplant professionals as well as transplant donors and recipients.